2021
DOI: 10.1186/s13005-021-00273-3
|View full text |Cite
|
Sign up to set email alerts
|

Class II correction by maxillary en masse distalization using a completely customized lingual appliance and a novel mini-screw anchorage concept – preliminary results

Abstract: Background The aim of the study was to evaluate the efficacy of a novel en masse distalization method in the maxillary arch in combination with a completely customized lingual appliance (CCLA; WIN, DW Lingual Systems, Germany). Therefore, we tested the null-hypothesis of a significant deviation from an Angle-Class I canine relationship and a normal overjet defined by an individual target set-up after dentoalveolar compensation in Angle Class II subjects. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…These findings regarding the CMA are fairly similar to those reported in the literature [19,20,22,23,26]. In our study, the overjet correction attained using the CMA i exhibits a comparatively modest degree of adjustment relative to outcomes reported in other studies for alternative Class II corrective modalities, such as the Forsus [29] appliance and mini screws [13]. These latter approaches yield results that align more closely with the findings associated with the Twin Block appliance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings regarding the CMA are fairly similar to those reported in the literature [19,20,22,23,26]. In our study, the overjet correction attained using the CMA i exhibits a comparatively modest degree of adjustment relative to outcomes reported in other studies for alternative Class II corrective modalities, such as the Forsus [29] appliance and mini screws [13]. These latter approaches yield results that align more closely with the findings associated with the Twin Block appliance.…”
Section: Discussionsupporting
confidence: 90%
“…The correction of Class II malocclusion can also be achieved by upper molar distalization through various methods, including the Pendulum [11], Carriere Motion 3D™ appliance [12], and mini screws [13,14]. The Carriere Motion 3D™ appliance (CMA; Henry Schein Orthodontics, Carlsbad, CA, USA) was introduced in 2004.…”
Section: Introductionmentioning
confidence: 99%
“…For maxillary en masse distal movement for dentoalveolar Class II correction, Beyling et al . [ 15 ] used a completely customized lingual appliance in combination with miniscrew anchorage and found that mean correction of the class II canine relationship of 0.43 mm per month from T1 to T2 was achieved with mini screw supported en masse distalization in an average of 10.5 ± 4.5 months (min. 5.2, max.…”
Section: Discussionmentioning
confidence: 99%
“…The micro-implants as anchorage can be successfully used for the treatment of Class II malocclusions [59]. OMIs were included in a novel en masse distalization concept used for patients with canine sagittal distalizations of half of a cusp or more.…”
Section: Use In Orthodontic Clinical Practice and Dento-facial Orthopedicsmentioning
confidence: 99%
“…The objective of the study was to get a complete en-masse distalization of the whole upper arch in one step. By maxillary tooth movements and dentoalveolar compensations, the canine neutral relationship and the overjet correction were achieved [59].…”
Section: Use In Orthodontic Clinical Practice and Dento-facial Orthopedicsmentioning
confidence: 99%